A toolbox for microbore liquid chromatography tandem-high-resolution mass spectrometry analysis of albumin-adducts as novel biomarkers of organophosphorus pesticide poisoning. (August 2018) - von der Wellen, Jens; Winterhalter, Peter; Siegert, Markus; Eyer, Florian; Thiermann, Horst; John, Harald
Highlights: Organophosphorus pesticides (OPP) form adducts with human serum albumin. Biomarkers containing phosphorylated tyrosine residues are produced by proteolysis with three proteases. Pronase produces a modified tyrosine residue, pepsin a modified hexadecapeptide and trypsin a tripeptide. Adducts were detected by liquid chromatography tandem-high-resolution mass spectrometry. Biomarkers of exposure were detected in plasma of OPP-poisoned patients. Abstract: Exposure to toxic organophosphorus pesticides (OPP) represents a serious problem in the public healthcare sector and might be forced in terroristic attacks. Therefore, reliable verification procedures for OPP-intoxications are required for forensic, toxicological and clinical reasons. We developed and optimized a toolbox of methods to detect adducts of human serum albumin (HSA) with OPP considered as long-term biomarkers. Human serum was incubated with diethyl-oxono and diethyl-thiono pesticides for adduct formation used as reference. Afterwards serum was subjected to proteolysis using three proteases separately thus yielding phosphorylated tyrosine residues (Y*) detected as single amino acid (pronase), as hexadecapeptide LVRY* 411 TKKVPQVSTPTL (pepsin) and as the tripeptide Y* 411 TK (trypsin), respectively. Adducts were analyzed via microbore liquid chromatography coupled to electrospray ionization (μLC-ESI) and tandem-high-resolution mass spectrometry (MS/HR MS). Using paraoxon-ethyl as model OPP for adduct formation, methods were optimized with respect to MS/HR MS-parameters, protease concentrations and incubation time for proteolysis. HSA-adducts were found to be stable in serum in vitro at +37 °C and −30 °C for at least 27 days and resulting biomarkers were stable in the autosampler at 15 °C for at least 24 h. Limits of identification of adducts varied between 0.25 μM and 4.0 μM with respect to the corresponding pesticide concentrations in serum. Applicability of the methods was proven by successful detection of the adducts in samples of OPP-poisoned patients thus demonstrating the methods as a reliable toolbox for forensic and toxicological analysis.